Endoscopic Detection of Gastric Metastases in Skin Melanoma - M. Yu. Kabanov; K. V. Sementsov; D. B. Degterev; M. Ya. Belikova; D. K. Savchenkov; T. E. Koshelev; A. K. Stechishina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. A clinical description of disseminated skin melanoma with endoscopic observation of its pathognomonic pigmented metastases into the stomach.Key points. A 66-yo patient was hospitalised with dyspnoea, general weakness, cough and suspected community-acquired pneumonia. The patient had a complex examination, including computed tomography, which revealed a presumed malignancy of the right lung with secondary changes in the chest and abdominal organs. Esophagogastroduodenoscopy (EGDS) visualised multiple pigmented spots and raised black plaques in cardia and the gastric body diagnosed as a metastasising melanoma in stomach. Endoscopic veriﬁcation of the metastases conﬁrmed the correct diagnosis of primary skin melanoma.Conclusion. Metastatic melanoma of the gastrointestinal tract has non-speciﬁc symptoms and most often occurs during the dissemination process. Endoscopy should be used to correctly verify pigmented mucosal lesions, necessarily allowing for non-pigmented gastric neoplasms in patients with skin melanoma in history.